IMPLEMENTASI MANAJAMEN PESERTA DIDIK DI SDN SUMBER AGUNG - Mutmainah; Encep Andriana; Siti Rokmanah (STKIP Subang, 2023)
This research was motivated by the lack of realization of student management programs due to the Covid-19 Pandemic. This research aims to analyze information regarding planning, acceptance of new students, division of student study groups, student development and training, as well as monitoring and evaluation of student management at SDN Sumber Agung. This research uses a qualitative approach by collecting data through interview techniques. The place of this research is SDN Sumber Agung, Jl. Bhayangkara No.48, Sumurpecung, Serang sub-district, Serang City. The research subject is one of the Sumber Agung Elementary School teachers in the 2023/2024 school year as a resource person. The results of the research show that planning, accepting new students, dividing student study groups, developing and training students, as well as monitoring and evaluating student management at SDN Sumber Agung are running effectively. The implementation of student management at SDN Sumber Agung runs effectively and in accordance with previously prepared plans.